THE RELATIONSHIP BETWEEN MINDSET AND INCOME LEVEL OF TRADITIONAL FISHERMEN COMMUNITIES IN SUNGAI UNDAN VILLAGERETEH SUB-DISTRICT INDRAGIRI HILIR REGENCY RIAU PROVINCE - Dina Noviana; Kusai Kusai; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Research on the Relationship between Mindset and the Income Level of Traditional Fishermen Communities held in March 2018 in Sungai Undan VillageReteh sub-District, Indragiri Hilir Regency, Riau Province. This study aims to find out how the mindset of the fishing community to find out how the level of income of fishermen and to find out how the relationship of mindset with the level of income of fishermen. The method used in this study is the survey method which is analyzed using Rank Spearman and the number of respondents in this study were 30 respondents who were processed using the SPSS 20 application. From the results of the research analysis, it was found that the mindset of the fishing community in Sungai Undan Village was seen from an indicator of mindset among group activities, the level of technology adoption, saving habits, confidence, educational orientation, gender mainstreaming, business orientation. From some indicators of the relationship between mindset of fishermen in Sungai Undan Village which have a real relationship with income with a value of rs = 0.583 ** group activity, the rate of technology adoption with a value of rs = 0.423 * confidence with a value of rs = 0.159 *, educational orientation with rs = 0,599 **, gender equalization with rs = 0,435 * and business orientation with rs = 0,500 **. Value on mindset indicators Group activities, technology adoption rates, self-confidence, educational orientation, gender mainstreaming, and business orientation are categorized as significant which means having a real relationship with income Keywords: Relationships, mindset, income level, traditional fishermen